Symposium 9: The Effects of a Blended Course Including Person Centered Encounter Groups on Students’ Learning, Relationships, and Teamwork - Motschnig-Pitrik, Renate (Proceedings of the International Conference on Networked Learning, 2006)
Recent educational strategies in the European Union encourage the development of attitudes and skills as a basis for knowledge development. In this paper we illustrate in which ways Person Centered education, developed by the American psychologist Carl Rogers to promote experiential, whole person learning, can be extended by employing new media. We describe the integration of new media into an academic course on Person-Centered Communication that includes encounter groups and virtual spaces for online communication and cooperation. Both the qualitative and the quantitative study confirmed that the vast majority of students learned significantly on the level of personal attitudes, social skills, and intellect and that online communication and support played a considerable, although not prominent role in their learning.